GOOD CORPORATE GOVERNANCE AND PROFITABILITY AS KEY FACTOR FOR DIVIDEND DISTRIBUTION DECISIONS - Sindi Lestari; Desniat Linsari Gulo; Vina Jasslyn Handayani; Widya Sari (Jurnal Mantik, 2022)
The discussion in this study aims to evaluate and examine how the influence of Good Corporate Governance on dividend distribution decisions with profitability as the moderating variable in companies in the consumer goods industry listed on the Indonesia Stock Exchange for the 2016-2020 period. There are a total of 209 population companies, including 128 consumer cyclical and 92 consumer noncyclical companies. Purposive sampling was used as the sampling method in this study. Secondary data was used in this study by collecting the required information from the annual report published through the official IDX website www.idx.com for the 2016-2020 period. Quantitative methods were used as the research technique with data analysis techniques based on the Partial Least Squares (PLS) model and SmartPLS software. The results of the discussion prove that institutional ownership has no impact on dividend policy, managerial ownership has no impact on dividend policy, independent commissioners has no impact on dividend policy, ROA-moderated managerial ownership with P-value = 0.456 has no impact on dividend policy, ROA-moderated independent commissioners with P-value = 0.757 have no impact on dividend policy, and ROA-moderated audit meetings where P-value = 0.009 has an impact on dividend policy, institutional ownership where P-value = 0.370 has no impact on ROA, managerial ownership where P-value = 0.005 has an impact on ROA, independent commissioners where P-value = 0.100 has no impact on ROA, audit meetings where P-value = 0.469 has no impact on ROA, and ROA where P-value = 0.033 has an impact on dividend policy